(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study identifies the communicative role of popular diplomacy through what is presented in the Turkish drama. It examines the Turkish drama serials’ effects on the Palestinian society. It mainly seeks to understand the negative consequences of these serials on the Palestinian culture and tradition. It is a survey research whose data is collected from two major Universities in Gaza (Al Aqsa University and Azhar University). A purposive sample of 200 male and female respondents, whose age group is 18-34, is selected. The cultivation theory is used and the results indicate that the Palestinian youth watch Turkish dramas with keenness and interest and are fascinated by the Turkish appealing culture. Besides, the results implied that the Turkish tele serials encourage sexual behavior, provoke pre as well as extra martial affair. These serials spread the culture of criminal activity, cause eve teasing, and support familial conflict. The study proposed a number of remedial measures which are inevitably needed to keep the Palestinian youth away from being blind followers of foreign cultures.